ОЦЕНКА ВЛИЯНИЯ ВЫБРОСОВ АВТОТРАНСПОРТНЫХ СРЕДСТВ В ОКРУЖАЮЩУЮ СРЕДУ В РЕСПУБЛИКЕ КАРАКАЛПАКСТАН - Казбеков, С.А.; Реймов, К.Д. (SCIENCE and SOCIETY, 2025)
The article discusses the issues of assessing the impact of vehicle emissions on the environment in the Republic of Karakalpakstan. It examines the main sources of air and soil pollution, as well as their effects on the ecosystem and human health. An increase in temperature leads to an expansion of the atmosphere and an increase in air volume, which contributes to the spread of pollution. The results obtained can be used to develop specific measures to reduce emissions and improve environmental quality.